11*1/3m=-1

Simple and best practice solution for 11*1/3m=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11*1/3m=-1 equation:


m in (-oo:+oo)

((1*11)/3)*m = -1 // + 1

((1*11)/3)*m+1 = 0

(11/3)*m+1 = 0

11/3*m+1 = 0 // - 1

11/3*m = -1 // : 11/3

m = -1/11/3

m = -3/11

m = -3/11

See similar equations:

| 7+6w=67 | | x^2+10=-21 | | -5x-1=-x+5 | | 1=2b+5 | | X-5/x=4 | | (3/8)+(-11/48) | | -3(a-4)=-3(2+7a) | | 3/5(4x-5)+3=30 | | x*x+10=6*3x | | 6z+5/7=7z+1/7 | | 2n-n=17n+14 | | (9*2w)+6w+5= | | 6(x+3)/5=3x-3 | | 7x-6+3x=-42 | | 26y-8+3y=16 | | -9x/x=0 | | x*x/7=w-y | | -14+2=-12x+8 | | l+l+l/2+2+l/2+2=22 | | -14=-3x-8 | | 7+3p-4(2p)+6= | | 30=5/9(x-32) | | 217=24x+7y | | 5x+14-4x=-7-12 | | d+d= | | n-(n+1)-(n+2)=-9 | | c=1.5x+11 | | -5(x-6)-8=22 | | 4l+4/2=22 | | 15x^2-49x+26= | | 7x(x+2y+4z)= | | 20-(x-8)+3x=6(x-3)+66 |

Equations solver categories